The Impact of Aphasia Severity on Spontaneous Speech: Why Is It Important to Assess Coherence and Informativeness? - Zuzana Zjarová; Viktória Kevická (Listy klinicke logopedie)
Spontaneous language production represents a fundamental form of communication in everyday interactions. In patients with aphasia, various aspects of spontaneous production are weakened, with the degree of impairment correlating with the severity of aphasia - ranging from mild to moderate to severe forms. However, there is still a lack of detailed knowledge regarding which specific areas of spontaneous speech are most affected depending on the degree of aphasia. The aim of this study is to comprehensively evaluate spontaneous production in patients with aphasia and to interpret the observed differences with respect to the severity of aphasia. Spontaneous production is analysed using the methodology of Spontaneous Speech Analysis (ASpoR), expanded with an assessment of coherence and informativeness, achieving a more comprehensive evaluation of the patient's abilities. The research sample consists of 40 individuals with aphasia, divided into two groups of mild and moderate aphasia. According to the results, significant differences exist between these groups in terms of productivity (the number of correctly expressed elementary text units), error rate (total number of phonological errors and grammatical agreement errors), coherence (both global and local), and informativeness (the number of main concepts and the core lexicon index). Based on the findings, it can be concluded that a comprehensive evaluation of spontaneous speech serves as a reliable indicator of aphasia severity,